2022
DOI: 10.3961/jpmph.21.396
|View full text |Cite
|
Sign up to set email alerts
|

Social and Policy Determinants of COVID-19 Infection Across 23 Countries: An Ecological Study

Abstract: Objectives: This study aimed to identify the social and policy determinants of coronavirus disease 2019 (COVID-19) infection across 23 countries.Methods: COVID-19 indicators (incidence, mortality, and fatality) for each country were calculated by direct and indirect standardization. Multivariable regression analyses were used to identify the social and policy determinants of COVID-19 infection.Results: A higher number of doctors per population was related to lower incidence, mortality, and fatality rates of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Furthermore, our study showed an inverse relationship between the ratio nurse per 10,000 and COVID-19 fatalities, suggesting that OECD states and partner countries with low ratio tended to have more COVID-19 fatalities. Another recent ecological study that searched to determine the predictors of SARS-CoV-2 infection also showed that the ratio nurses/midwives per population was inversely associated with COVID-19 mortality [ 31 ]. Nurses are among frontliners to safeguard the lives of affected persons during health crises.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study showed an inverse relationship between the ratio nurse per 10,000 and COVID-19 fatalities, suggesting that OECD states and partner countries with low ratio tended to have more COVID-19 fatalities. Another recent ecological study that searched to determine the predictors of SARS-CoV-2 infection also showed that the ratio nurses/midwives per population was inversely associated with COVID-19 mortality [ 31 ]. Nurses are among frontliners to safeguard the lives of affected persons during health crises.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers are more associated with COVID-19 morbidity than non-smokers [ 32 , 33 ]. Even though there was a study [ 22 ] reports that a significant difference in the morbidity of COVID-19 between smokers and non-smokers was absent, the results of our study cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to share some ideas related to the recently published article, “Social and Policy Determinants of COVID-19 Infection Across 23 Countries: An Ecological Study” [ 1 ]. Coronavirus disease 2019 (COVID-19) transmission can be influenced by social and policy determinants, such as integrated health systems and policy responses to COVID-19, according to Kim et al [ 1 ]. When responding to COVID-19, a variety of socioeconomic and policy issues should be taken into account [ 1 ].…”
mentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) transmission can be influenced by social and policy determinants, such as integrated health systems and policy responses to COVID-19, according to Kim et al [ 1 ]. When responding to COVID-19, a variety of socioeconomic and policy issues should be taken into account [ 1 ]. We agree that any disease can be impacted by local socioeconomic and policy factors.…”
mentioning
confidence: 99%